The Torres Strait Treaty: A possible solution to the Aegean conflict - Panagiotis Pantazis (CES Working Papers, 2022)
The Aegean conflict constitutes a dispute that has been affecting Greek-Turkish bilateral relations for the last five decades. It involves elements such as sovereignty, sovereign rights and national security. This paper suggests that the Torres Strait Treaty, an international agreement that provides the framework for the management of Australia and Papua New Guinea's (PNG) maritime boundaries, can be utilised to provide a possible solution to the Aegean conflict. The resolution of the Aegean conflict would improve the political and diplomatic relations between Greece and Turkey, guarantee the security of the Aegean region and allow for the two countries to benefit from economic cooperation.
Keywords: 330; international law; conflict resolution; bilateral relations